Distinctive Under-Expression Profile of Inflammatory and Redox Genes in the Blood of Elderly Patients with Cardiovascular Disease - Milanesi E; Manda G; Dobre M; Codrici E; Neagoe IV; Popescu BO; Bajenaru OA; Spiru L; Tudose C; Prada GI; Davidescu EI; Piñol-Ripoll G; et al. (Dove Medical Press, 2021)
Elena Milanesi,1 Gina Manda,1 Maria Dobre,1 Elena Codrici,1 Ionela Victoria Neagoe,1 Bogdan Ovidiu Popescu,1– 3 Ovidiu Alexandru Bajenaru2,4 †, Luiza Spiru,2,5 Catalina Tudose,2,6 Gabriel-Ioan Prada,2,7 Eugenia Irene Davidescu,2,3 Gerard Piñol-Ripoll,8 Antonio Cuadrado1,9– 12 1“Victor Babes” National Institute of Pathology, Bucharest, 050096, Romania; 2Clinical Neurosciences, Geriatrics and Gerontology Departments, “Carol Davila” University of Medicine and Pharmacy, Bucharest, 020021, Romania; 3Neurology Department, Clinical Hospital Colentina, Bucharest, 020125, Romania; 4Neurology Department, University Emergency Hospital, Bucharest, 050098, Romania; 5The Excellence Memory Center and Longevity Medicine, “Ana Aslan” International Foundation,, Bucharest, 050064, Romania; 6Section II, “Prof. Dr. Al. Obregia” Psychiatry Clinical Hospital & the Memory Center of the Romanian Alzheimer Society, Bucharest, 041914, Romania; 7Section IV, “Ana Aslan” National Institute of Gerontology and Geriatrics, Bucharest, 011241, Romania; 8Unitat Trastons Cognitius, Hospital Universitari Santa Maria-IRBLLeida, Lleida, 25198, Spain; 9Department of Endocrine Physiology and Nervous System, Instituto de Investigaciones Biomédicas “Alberto Sols” UAM-CSIC, Madrid, 28029, Spain; 10Department of Biochemistry, Faculty of Medicine, Autonomous University of Madrid, Madrid, 28049, Spain; 11Neuroscience Section, Instituto de Investigación Sanitaria La Paz (IdiPaz), Madrid, 28046, Spain; 12Centro de Investigación Biomédica en Red Sobre Enfermedades Neurodegenerativas (CIBERNED), ISCIII, Madrid, 28031, Spain†Prof. Ovidiu A. Bajenaru passed away on 03.09.2020Correspondence: Gina Manda“Victor Babes” National Institute of Pathology, 99-101 Splaiul Independentei, Bucharest, 050096, RomaniaTel +40 744246887Fax +40 21 3194528Email gina.manda@gmail.comAntonio CuadradoInstituto de Investigaciones Biomédicas “Alberto Sols” UAM-CSIC, C/Arturo Duperier 4, Madrid, 28029, SpainTel +34 638 29 65 85Fax +34 915 85 44 01Email antonio.cuadrado@uam.esPurpose: Chronic low-grade inflammation and oxidative stress are present in most of the pathologic mechanisms underlying non-communicable diseases. Inflammation and redox biomarkers might therefore have a value in disease prognosis and therapy response. In this context, we performed a case–control study for assessing in whole blood the expression profile of inflammation and redox-related genes in elderly subjects with various comorbidities.Patients and Methods: In the blood of 130 elderly subjects with various pathologies (cardiovascular disease, hypertension, dyslipidemia including hypercholesterolemia, type 2 diabetes mellitus), kept under control by polyvalent disease-specific medication, we investigated by pathway-focused qRT-PCR a panel comprising 84 inflammation-related and 84 redox-related genes.Results: The study highlights a distinctive expression profile of genes critically involved in NF-κB-mediated inflammation and redox signaling in the blood of patients with cardiovascular disease, characterized by significant down-regulation of the genes NFKB2, NFKBIA, RELA, RELB, AKT1, IRF1, STAT1, CD40, LTA, TRAF2, PTGS1, ALOX12, DUOX1, DUOX2, MPO, GSR, TXNRD2, HSPA1A, MSRA, and PDLIM1. This gene expression profile defines the transcriptional status of blood leukocytes in stable disease under medication control, without discriminating between disease- and therapy-related changes.Conclusion: The study brings preliminary proof on a minimally invasive strategy for monitoring disease in patients with cardiovascular pathology, from the point of view of inflammation or redox dysregulation in whole blood.Keywords: aging-related diseases, cardiovascular disease, inflammation, NF-κB signaling, redox metabolism, oxidative stress